Some Wild Mushrooms with High Antioxidant Capacity Exhibit Potent Anticancer Activity on Cancer Cells using the Apoptotic and Antimigration Cell Death Mechanisms - Şebin, Murat; Yılmaz, Necmettin; Aydın, Ali (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Aim: This study aims to provide in vitro experimental evidence that wild mushrooms have the potential to be used as a pharmaceutical that could be effective against various types of cancer. Background: Throughout human history, besides food, traditional medicine and natural poisons obtained from mushrooms have been used for the treatment of many diseases. Clearly, edible and medicinal mushroom preparations have beneficial health effects without the known severe adverse side effects. Objectives: This study was designed to reveal the cell growth inhibitory potential of five different edible mushrooms and the biological activity of Lactarius zonarius was shown here for the first time. Methods: The mushrooms fruiting bodies were dried and powdered then extracted with hexane, ethyl acetate, and methanol. The mushroom extracts were screened for possible antioxidant activities by the free radical scavenging activity (DPPH) method. Antiproliferative activity and cytotoxicity of the extracts were investigated in vitro on A549 (human lung carcinoma), HeLa (human cervix carcinoma), HT29 (human colon carcinoma), Hep3B (human hepatoma), MCF7 (human breast cancer), FL (human amnion cells), and Beas2B (normal human cells) cells lines by using MTT cell proliferation assay, lactate dehydrogenase (LDH) assay, DNA degradation, TUNEL, and cell migration assay. Results: Using proliferation, cytotoxicity, DNA degradation, TUNEL, and migration assay, we displayed that hexane, ethyl acetate, and methanol extracts of the Lactarius zonarius, Laetiporus sulphureus, Pholiota adiposa, Polyporus squamosus, and Ramaria flava were effective on the cells even so at low doses (< 45.0 - 99.6 µg/mL) by acting in a way that represses migration, as a negative inducer of apoptosis. It was also demonstrated that mushroom extracts with high antioxidant effect have within the acceptable cytotoxic activity of 20%-30% on the cell membrane at concentrations higher than 60 µg/mL. Overall, all of the mushroom extracts with high antioxidant effects had strong antiproliferative activity and low toxicity for cells. These findings, at least, highlight that these mushroom extracts can be used for the treatment of cancer disease, especially as a supportive therapy against colon, liver, and lung cancer.
Keywords: wild mushrooms